Determinants of Leverage in Emerging Markets: Empirical Evidence - Chen, Yarong; Sensini, Luca; Vazquez, Maria (International Journal of Economics and Financial Issues, 2021)
The purpose of this paper is to investigate the relationship between leverage and its main determinants in the Argentine context, using the trade-off theory and the pecking order theory. Studies that have addressed this issue in emerging economies are still quite rare and the results are incomplete and controversial. To identify the companies to be analyzed, we used a stratified sampling methodology, following an economic criterion. The balance sheet data were collected through a questionnaire and were normalized to neutralize the effects of high inflation. The period analyzed is 3 years and concerns 181 companies. The research hypotheses were tested using a static fixed effects (FE) model. The results of this paper contribute to the existing literature, providing further empirical evidence on the financial behaviour of firms in an as yet unexplored economic context. Furthermore, empirical findings can be useful for Argentine entrepreneurs and managers of companies to improve their financial decisions. Keywords: Capital structure, Leverage, Profitability, Business Risk, Emerging Markets JEL Classifications: G32, M16, M21 DOI: https://doi.org/10.32479/ijefi.10997